An Analysis of the Process of Capital Liberalization in Italy - Bodnar, Gordon (IMF Working Papers; Working Paper ;, 1992)
Beginning in 1985 Italy embarked on a path of progressive removal of its system of controls on portfolio investment, a process formally completed with the abolition of all remaining restrictions in 1990. In this paper we review this policy of capital liberalization and integrate the analysis with an examination of the process of stabilization of the lira exchange rate in the 1980s. Various indicators of capital controls' effectiveness and target zone credibility are used to identify the temporal relations among capital liberalization, exchange rate stabilization and capital flows.